2020
DOI: 10.1007/s40615-020-00763-1
|View full text |Cite
|
Sign up to set email alerts
|

Interventions to Reduce Healthcare Disparities in Cancer Screening Among Minority Adults: a Systematic Review

Abstract: BackgroundRacial minority populations face an increased burden relative to cancer interventions. Compared to Caucasians, the cancer screening rate is substantially lower among African American, Asian American, Latinx American, and American Indian/Alaska Native populations. Barriers such as low health literacy, lack of health insurance, and miscommunication between patients and providers have been identified as important factors that result in low screening rates among minority adults. This study was to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 74 publications
0
32
0
Order By: Relevance
“…High Blood Pressure-Health Literacy (HBP-HL) refers to the ability of hypertensive patients to acquire, understand, and deal with hypertension-related knowledge as well as the medical services needed to control diseases [ 15 ]. Previous studies have indicated HBP-HL as a powerful indicator for predicting the health status of people, which is highly correlated with morbidity, mortality, life expectancy, and HRQoL of people with hypertension [ 16 ], especially in ethnic minorities [ 17 , 18 ]. Low health literacy usually leads to a series of negative health outcomes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…High Blood Pressure-Health Literacy (HBP-HL) refers to the ability of hypertensive patients to acquire, understand, and deal with hypertension-related knowledge as well as the medical services needed to control diseases [ 15 ]. Previous studies have indicated HBP-HL as a powerful indicator for predicting the health status of people, which is highly correlated with morbidity, mortality, life expectancy, and HRQoL of people with hypertension [ 16 ], especially in ethnic minorities [ 17 , 18 ]. Low health literacy usually leads to a series of negative health outcomes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…High Blood Pressure-Health Literacy (HBP-HL) refers to the ability of hypertensive patients to acquire, understand, and deal with hypertension-related knowledge as well as the medical services needed to control diseases [11] . Previous studies have indicated HBP-HL as a powerful indicator for predicting the health status of people, which is highly correlated with morbidity, mortality, life expectancy, and HRQoL of people with hypertension [12] , especially in ethnic minorities [13][14] . Low health literacy usually leads to a series of negative health outcomes [15] .…”
mentioning
confidence: 99%
“…Referring to the G*power 3.1.9.7 software (linear multiple regression: fixed model, R 2 increase), a minimal number of 154 participants was required to reach significance when considering the following statistical parameters: type I error α = 5%, power 1-β = 95%, a moderate effect size f 2 = 0.15, and a total number of variables N = 15 to be integrated in the multivariable regression analysis [37,38]. Given the lack of consensus in the sample size recommendations for the Structural Equation Modelling (SEM), we used Kline (2015) criteria that had 20 observations (participants) for each estimated parameter in the model, with a typical size of N = 200, among models using the maximum likelihood method [39]. However, recently, several studies recommended a sample size which would vary from 50 to 400 participants [40][41][42].…”
Section: Minimum Sample Size Calculationmentioning
confidence: 99%
“…However, many of these studies did not use theory in their interventions. Those that did use theory drew from social cognitive theory, the health belief model, the transtheoretical model, the social support model, elaboration theory, or multiple theories [39][40][41][42]. In sum, there are limited studies to increase cervical cancer screening among minority women and only a few of these interventions among minority women utilized theory.…”
Section: Introductionmentioning
confidence: 99%